Gold-based alloy solder and its manufacturing method

The gold-based alloy solder material, with optimized dimensions and an alkaline electrolytic degreasing treatment, addresses the challenge of uniform wettability and prevents leakage and short circuit failures in miniaturized electronic components, ensuring reliable solder joints.

JP7669716B2Active Publication Date: 2025-04-30SUMITOMO METAL MINING CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021027960
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-24
Publication Date
2025-04-30
Estimated Expiration
2041-02-24

AI Technical Summary

Technical Problem

The miniaturization of electronic components, such as quartz devices and SAW filters, has led to challenges in maintaining uniform wettability and preventing leakage and short circuit failures due to uneven solder alloy distribution during the soldering process.

Method used

A gold-based alloy solder material with a frame shape and dimensions optimized for small-sized electronic components, characterized by a maximum height after melting and solidifying within twice the initial thickness, and subjected to an alkaline electrolytic degreasing treatment to ensure uniform wetting and prevent organic residue inhibition.

Benefits of technology

The gold-based alloy solder material effectively maintains shape accuracy and prevents leakage and short circuit failures by ensuring uniform wettability and consistent solder joint formation, even with reduced solder volumes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669716000003
    Figure 0007669716000003
  • Figure 0007669716000004
    Figure 0007669716000004
  • Figure 0007669716000005
    Figure 0007669716000005
Patent Text Reader

Abstract

To provide a gold-based alloy solder material which prevents leakage failures and short-circuit failures of an electrode wire due to non-uniform wettability deterioration in melting in a solder material used in sealing a downsized component of an electronic device such as a crystal device and a SAW filter, and can obtain more uniform wettability.SOLUTION: A solder material for electronic component bonding, which is made of a gold-based alloy, and has a frame shape with a size of 1.2 mm square or less and a thickness of 0.02 mm or less, or a ring shape with a size of φ1.2 mm or less and a thickness of 0.02 mm or less, has a maximum height of the solder material after having been melted and solidified by heating of twice or less a thickness of the solder material before heating.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gold-based alloy solder material used for joining electronic components mounted on electronic devices and the like, and a method for producing the same. [Background technology]

[0002] Solder materials made of various metal compositions are widely used for joining electronic components, etc. Among these types of solder materials, those mainly composed of gold have been generally used for packages where sealing performance is important. Examples include Au / 20Sn alloy, Au / 1-3.15Si alloy, and Au / 12Ge alloy. These are appropriately selected and used depending on the purpose and the metal to be joined.

[0003] In the manufacturing method of this type of solder material, as described in Patent Document 1, for example, the desired metals are first mixed in the desired ratio, melted and alloyed, and then the alloy is formed into a thin plate by continuous casting to produce a master alloy. Then, the solder material is rolled using a warm rolling device that can control the rolling temperature to obtain a ribbon-shaped solder material. Finally, the solder material is finished into a desired shape by punching using a press or the like. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-283094 A Summary of the Invention [Problem to be solved by the invention]

[0005] Recently, as smartphones have become more sophisticated, the size of electronic device components, such as quartz devices and SAW filters, used in these devices is becoming smaller and smaller. Au-Sn alloy solder material is mainly used for sealing the packages of quartz devices and SAW filters. The solder materials used in the manufacture of these electronic devices are required to be able to maintain their shape with high precision when heated, melted, and solidified. For example, the packages of quartz devices that house quartz crystal units have recently shifted from 1210 (1.2 x 1.0 mm) size to 1008 (1.0 x 0.8 mm) size for the most advanced products. A frame-shaped Au-Sn alloy solder material is used to seal the opening of a quartz crystal device, but if the bonding surface along the periphery of the opening is not uniformly wetted with the Au-Sn alloy during sealing, problems such as leaks may occur. Furthermore, if the solder alloy spreads unevenly when melted, it may flow into the inside of the package through the opening, and the flowed-in solder alloy may cause a short circuit of electrode wiring or the like.

[0006] Furthermore, as electronic components such as crystal devices become smaller, the size and thickness of the solder material used to join the electronic components are also becoming smaller, resulting in a smaller volume. Conventionally, the thickness of solder material was around 0.03 mm, but as crystal devices become smaller, solder material with a thickness of 0.02 mm or less is being used, and in some cases, solder material with a thickness of 0.015 mm or less is also being used. If such a solder material with a reduced volume were to develop the above-mentioned uneven wetting and spreading or to flow out of areas other than the joining surface when melted, the volume of the solder material that is actually responsible for sealing and joining would become smaller and smaller in a solder joint where sealing and joining are already performed with a limited solder volume, and the problem of the reliability of the solder joint being impaired would become even more pronounced. For this reason, solder materials are required to have more uniform wettability.

[0007] The present invention has been made in consideration of the above problems, and aims to provide a gold-based alloy solder material that can prevent leak defects and short-circuit defects of electrode wiring caused by uneven deterioration of wettability during melting in solder materials used for sealing miniaturized parts of electronic devices, such as crystal devices and SAW filters, and can obtain more uniform wettability, and a method for producing the same. [Means for solving the problem]

[0008] The gold-based alloy solder material according to the present invention is made of a gold-based alloy, Dimensions is 1.2mm square or less, thickness is 0.02mm or less , frame width is 0.15mm or less Frame shape, or Outside diameter The solder material for joining electronic components has a ring shape with a diameter of φ1.2 mm or less and a thickness of 0.02 mm or less, and is characterized in that the maximum height of the solder material after it is heated to melt and solidify is within twice the thickness of the solder material before heating.

[0009] Furthermore, it is preferable that the gold-based alloy solder material of the present invention has a frame shape, and the difference in height between the four corners of the solder material after it has been heated to melt and solidify is equal to or less than the thickness of the solder material before heating.

[0010] Furthermore, it is preferable that the gold-based alloy solder material of the present invention has a frame shape, and the maximum width of the four corners of the solder material after it has been heated to melt and solidify is within twice the width of the four corners of the solder material before heating.

[0011] In addition, the gold-based alloy solder material of the present invention is made of an Au-Sn alloy, Dimensions is 1.0mm corner It is preferable that the frame has a thickness of 0.015 mm or less and a frame width of 0.15 mm or less.

[0012] The method for producing a gold-based alloy solder material according to the present invention is a method for producing a solder material for joining electronic components, which is mainly composed of gold. Sn Mix in the desired ratio and dissolve. Au-20wt%Sn alloy Create The solder material is then cast into a thin plate and rolled into a ribbon shape. Using a sodium hydroxide solution, the solder material is set as the cathode and 0.7 to 7 A / dm 2 At a current density of After alkaline electrolytic degreasing, the material is shaped. Dimensions is 1.2mm square or less, thickness is 0.02mm or less , frame width is 0.15mm or less Frame shape, or Outside diameter The ring shape is φ1.2mm or less and the thickness is 0.02mm or less. By doing so, we can manufacture solder material whose maximum height after heating, melting and solidifying is within twice the thickness of the solder material before heating. It is characterized by the following.

[0013] In the method for producing the gold alloy solder material of the present invention, the alkaline electrolytic degreasing treatment is preferably carried out in two stages.

[0014] In the method for producing the gold-based alloy solder material of the present invention, the alkaline electrolytic degreasing treatment is carried out at a current of 2 to 5 A / dm 2 It is preferable to apply the current density of 1000 .mu.m.

[0015] In addition, in the method for producing a gold-based alloy solder material of the present invention, the solder material after the shaping process is Dimensions is 1.0mm corner It is preferable that the frame has a thickness of 0.015 mm or less and a frame width of 0.15 mm or less. Effect of the Invention

[0016] According to the present invention, a gold-based alloy solder material can be obtained that can prevent leak defects and short-circuit defects of electrode wiring caused by uneven deterioration of wettability during melting in solder material used for sealing miniaturized parts of electronic devices, such as quartz devices and SAW filters, and can provide more uniform wettability, as well as a manufacturing method thereof. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a schematic diagram showing the shape of the gold-based alloy solder of the present invention after it has been heated to melt and solidify. [Diagram 2] FIG. 2 is a schematic diagram showing the shape of a gold-based alloy solder material produced by a conventional manufacturing method after it has been heated to melt and solidify. [Diagram 3] FIG. 2 is a diagram showing measurement points for height and width of solder materials in an example and a comparative example after the solder materials are heated, melted, and solidified. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The gold-based alloy solder material of the present invention is used for joining electronic components and the like, and is particularly used for sealing packages of crystal devices, SAW filters, and the like, where sealing properties are important. Solder materials used in packaging for quartz devices, SAW filters, etc. are generally made mainly of gold, as their sealing performance is important, such as Au / 20Sn alloy, Au / 1~3.15Si alloy, and Au / 12Ge alloy. The gold-based alloy solder material of the present invention is not limited to the above composition, and may be of any composition as long as it contains gold as the main component. The gold-based alloy solder material of the present invention will be described below by taking an Au-Sn alloy solder material as an example. The gold-based alloy solder material of the present invention is not a solder material plated with Au as described in Patent Document 1, but is used for joining electronic components without Au plating on the upper and lower surfaces of the solder material.

[0019] The size and thickness of solder materials used to join electronic components, etc., are becoming smaller as the size of electronic components, such as quartz crystal devices and SAW filters, becomes smaller. For example, the size of quartz crystal device packages that house quartz crystal units has recently shifted from 1210 (1.2 x 1.0 mm) to 1008 (1.0 x 0.8 mm) in the most advanced packages. A frame-shaped solder material is used to seal the opening of a quartz crystal device, but if the joining surface along the periphery of the opening is not uniformly wetted during sealing, problems such as leak defects may occur. In addition, if the solder alloy spreads unevenly when melted, it may flow into the inside of the package from the opening, and the flowed-in solder alloy may short-circuit the electrode wiring, etc. Furthermore, as the components of the quartz crystal device become smaller, the size and thickness of the solder material used to join the miniaturized components also become smaller, and the volume of the solder material becomes smaller. If such a small-volume solder material causes the uneven wetting and spreading or flows out to areas other than the joining surface when melted, the volume of the solder material that is actually responsible for sealing and joining in the solder joint where sealing and joining are already performed with a limited solder volume becomes smaller and smaller, and the problem of the reliability of the solder joint being impaired becomes even more pronounced. For this reason, the solder material used in the manufacture of these electronic devices is required to have more uniform wettability, and in particular, it is required that the small-volume solder material be able to maintain its shape with high precision when melted.

[0020] The gold-based alloy solder material of the present invention is compatible with the miniaturization of the above-mentioned packages, Dimensions has a frame shape of 1.2 mm square or less; or Outside diameter The gold-based alloy solder material of the present invention may have a ring shape with a diameter of φ1.2 mm or less. The thickness is 0.02 mm or less. The gold-based alloy solder material of the present invention is a solder material that has been miniaturized to accommodate the miniaturization of packages, and when the solder volume is small, it exhibits a remarkable effect of maintaining the shape when melted. Furthermore, the gold-based alloy solder material of the present invention is Dimensions The effect is more pronounced when the solder material has a frame shape of 1.0 mm square or less, a thickness of 0.015 mm or less, and a frame width of 0.15 mm or less. The solder material generally has a frame shape, and the volume of the corners varies greatly. Therefore, the gold-based alloy solder material of the present invention has an effect of maintaining its shape when melted when it has a frame shape, but also has a similar effect when it has a ring shape.

[0021] Fig. 1 shows a schematic diagram of the shape of the gold-based alloy solder of the present invention after it has been heated, melted, and solidified. Fig. 2 shows a schematic diagram of the shape of the gold-based alloy solder produced by a conventional manufacturing method after it has been heated, melted, and solidified. As shown in Figure 2, when gold-based alloy solder material produced using a conventional manufacturing method is heated and melted, the frame shape is easily distorted. For example, as shown in Figure 2(a), one corner (here, the lower left) bulges compared to the other corners and leaks to the inside of the frame. Also, as shown in Figure 2(b), one corner (here, the lower left) bulges and the lower and upper left corners leak inside and outside the frame. As described above, with gold-based alloy solder material produced using conventional manufacturing methods, the frame shape is easily distorted when melted, and in the case of a frame shape in particular, the corners tend to become raised and the solder material tends to collect around the corners. This was discovered by the present inventors as a result of repeated tests in which gold-based alloy solder material produced using conventional manufacturing methods to form a frame shape of a size corresponding to the miniaturization of packages was heated, melted, and solidified.

[0022] In addition, the inventors of the present invention have found that some of the gold-based alloy solder materials produced using the conventional manufacturing method contained organic residues, which hindered the solder material from spreading, causing the variation. It is presumed that the organic residues in some of the solder materials hindered the solder material from spreading, causing the solder material to concentrate and swell at the corners and gather around the corners. Therefore, the present inventors have devised a method for producing the gold-based alloy solder material of the present invention, in which a solder material formed into a ribbon shape by warm rolling is subjected to an alkaline electrolytic degreasing treatment, and then the solder material is shaped into a predetermined shape, as described below. As in the manufacturing method of the gold-based alloy solder material of the present invention, by carrying out an alkaline electrolytic degreasing treatment and then carrying out shaping to process into a predetermined shape, organic residues on the surface of the solder material can be removed to give a uniform surface. This prevents the gold-based alloy solder material obtained by the manufacturing method of the present invention from being hindered in spreading when melted, thereby obtaining uniform wettability.

[0023] Fig. 1 is a schematic diagram showing the shape of the gold-based alloy solder of the present invention, which is produced using the manufacturing method of the gold-based alloy solder of the present invention, after it has been heated, melted, and solidified. As shown in Fig. 1, the gold-based alloy solder of the present invention does not have any bulges at the corners that would destroy the frame shape, and leakage into and out of the frame is kept to a minimum, and the solder can maintain its shape with high precision even after it has been heated, melted, and solidified. In addition, the material in Figures 1 and 2 is an Au-Sn alloy. External dimensions Solder material having a frame shape of 1 mm × 0.8 mm, 0.015 μm thick, and 0.07 mm wide was prepared in a similar manner to Example 1 described later in FIG. 1 and Comparative Example 1 described later in FIG. 2. The prepared solder material was tested under the heating conditions of Example 1 described later and the shape of the sample was shown typically. As mentioned above, deformation of the solder material is likely to occur at the corners of the frame. Table 1 shows the height of the corners of the frame shape after the solder material is heated, melted, and solidified, and Table 2 shows the width of the corners of the frame shape. As shown in Table 1, the maximum height of the corners of the frame shape after the solder material is heated, melted, and solidified is more than twice the thickness of the solder material for the comparative example gold-based alloy solder material produced using the conventional manufacturing method. In contrast, the gold-based alloy solder of the present invention is produced by applying alkaline electrolytic degreasing and then shaping, so that the maximum height of the corners of the frame shape after the solder is heated to melt and solidify is controlled to within 2 times the thickness of the solder before heating. Furthermore, by setting more appropriate conditions for the alkaline electrolytic degreasing, as described below, it is possible to control the maximum height to within 1.5 times the thickness of the solder before heating. In addition, when the gold-based alloy solder material of the present invention was checked for the difference between the maximum and minimum values ​​of the four corners of the frame shape after the gold-based alloy solder material was heated to melt and solidify, the gold-based alloy solder material of the present invention was approximately half or less than that of the gold-based alloy solder material of the comparative example produced using a conventional manufacturing method, and was kept below the thickness of the solder material before heating, and the height of the four corners was maintained approximately uniform. The average value of the height of the four corners was approximately the same. From this, it is presumed that the gold-based alloy solder material of the comparative example produced using the conventional manufacturing method has a phenomenon in which the volume of some corners increases and the volume of the other corners decreases. Similarly, the maximum width of the corners of the frame shape after the gold-based alloy solder material is heated, melted, and solidified can be kept within twice the set width of the solder material.

[0024] Next, a method for producing the gold-based alloy solder material of the present invention will be described. As described above, the manufacturing method of the gold-based alloy solder material of the present invention is to mix the desired metals in the desired ratio with gold as the main component, melt them to form an alloy, and form a thin plate by continuous casting to produce a master alloy. Then, the plate is rolled using a warm rolling device that can control the temperature during rolling to obtain a ribbon-shaped solder material. Finally, the plate is punched out using a press or the like to obtain a solder material in the form of a ribbon. Dimensions Frame shape with a square of 1.2 mm or less and a thickness of 0.02 mm or less, or Outside diameter The wire is finished into a ring shape with a diameter of 1.2 mm or less and a thickness of 0.02 mm or less.

[0025] In the case of alloy solder materials mainly composed of Au, since the Au intermetallic compound is difficult to process, warm processing is generally performed in the rolling process. For example, in the case of Au / 20Sn solder materials, the Sn contained in the solder material is likely to be naturally oxidized by reaction with oxygen in the air, and the formation of an oxide film is easily promoted by the roll heat and friction heat received during the warm rolling process in the manufacturing process, and an oxide film of Sn is formed on the surface of the solder material. It has been confirmed that when a solder material with an oxide film of Sn formed on its surface is used for joining, the wet spread of the solder material is hindered due to the influence of this oxide film. Therefore, in the past, a cleaning process using an organic solvent was performed before finishing into a predetermined shape, but as described above, the inventors of the present invention investigated and found that there was organic residue on a part of the solder member, which hindered wet spread and caused variation. In the method for producing the gold-based alloy solder material of the present invention, the solder material formed into a ribbon shape after warm rolling is subjected to alkaline electrolytic degreasing treatment, and then is shaped into a desired shape.

[0026] The method for producing the gold-based alloy solder material of the present invention will be described in detail below. Solder material is made by mixing the desired metals in the desired ratios, with gold as the main component, melting and alloying them, and then forming them into thin plates using a continuous casting method to produce master alloys.Then, using a warm rolling device that can control the temperature during rolling, the plate is rolled to the desired thickness to obtain ribbon-shaped solder material. In the method for producing the gold-based alloy solder material of the present invention, the ribbon-shaped solder material is subjected to an alkaline electrolytic degreasing treatment. Alkaline electrolytic degreasing is an electrochemical surface treatment that can reduce the oxide film formed during the manufacturing process of solder material and remove organic residues. Anode and cathode electrodes are placed in an electrolyte solution and a rectified voltage is applied. When a voltage is applied to the solder material as the cathode, hydrogen is generated from the solder material, and the oil is physically stripped off. In addition, since a reducing atmosphere is created in the solution, the surface of the solder material is activated and the oxide film is reduced. It is efficient and desirable to perform alkaline electrolytic degreasing on ribbon-shaped solder material immediately before the solder material is processed into a specified shape.

[0027] In the alkaline electrolytic degreasing process, the alkaline electrolytic degreasing step, the first water rinsing step, the neutralization step, and the second water rinsing step are performed in this order. By performing these steps in order, the treatment efficiency for the surface of the solder material is improved, and the treatment speed can be increased. The alkaline electrolytic solution used in the alkaline electrolytic degreasing step is not particularly limited, but for example, a solution containing sodium hydroxide as the main component and pure water as the remainder is used. The current density during alkaline electrolysis is set in the range of 2 to 5 A / dm 2 It is preferable that the current density is 2A / dm 2 If the current density is less than 5A / dm, the effect of electrolytic degreasing is not sufficient. 2 If the solder material is thin, there is a risk of the solder material being deformed when the pressure exceeds this value. In the neutralization process, since the surface of the solder material is alkaline after the alkaline electrolytic degreasing process, it is neutralized with an acid, etc. Existing technology can be used for the neutralization process. Furthermore, after the alkaline electrolytic degreasing process and the neutralization process, liquid residue remains on the surface of the solder material, so it is desirable to rinse the surface of the solder material with water in a water rinsing process (a first water rinsing process after the alkaline electrolytic degreasing process and a second water rinsing process after the neutralization process).

[0028] Furthermore, it is preferable to carry out the alkaline electrolytic degreasing treatment in two stages. In the two-stage alkaline electrolytic degreasing treatment, the alkaline electrolytic degreasing step, the first water washing step, the alkaline electrolytic degreasing step, the first water washing step, the neutralization step, and the second water washing step are carried out in this order. The step of forming the ribbon-shaped solder material is the rolling step, and if the rolling lubricant used in the rolling step is carried into the washing step, the rolling lubricant may remain in the solution and become organic residue. Therefore, it is decided to carry out the alkaline electrolytic degreasing treatment in two stages, and in the first stage alkaline electrolytic degreasing step, degreasing is mainly performed, such as removing the lubricant, and the oil on the material surface is removed to remove the oil and make it somewhat clean, and then the second stage alkaline electrolytic degreasing step is carried out, which makes it possible to reduce the oxide film on the surface and reliably remove the organic residue.

[0029] It is preferable to remove moisture after the water washing step by drying the material by blowing clean air through a high-performance filter, etc. Furthermore, drying efficiency can be improved and the processing speed can be increased by quickly drying the material by irradiating it with hot air or using a far-infrared heater, etc.

[0030] As described above, the gold-based alloy solder of the present invention is obtained by subjecting the solder formed into a ribbon shape to alkaline electrolytic degreasing treatment and then shaping to the above-mentioned predetermined shape, and the oxide film on the surface of the solder is temporarily removed by alkaline electrolytic degreasing treatment, thereby suppressing the thickness of the oxide film that will be formed thereafter and making the surface of the solder uniform. As a result, when the solder processed into the predetermined shape is heated and melted for use in sealing, more uniform wettability is obtained. EXAMPLES

[0031] Specific examples to which the present invention is applied will be described below, but the present invention is not limited to these examples.

[0032] Au (purity 99.99wt%) and Sn (purity 99.99wt%) were used as the raw materials for the solder material, and melting and casting were performed to produce an Au-20wt%Sn ingot. The material was then warm-rolled at a material temperature of 250°C to obtain a ribbon-shaped solder material with a width of 50mm and a thickness of 0.025mm.

[0033] In Example 1, the alkaline electrolytic degreasing treatment was performed in two stages. The two-stage alkaline electrolytic degreasing treatment was configured to perform an alkaline electrolytic degreasing step, a first water washing step, an alkaline electrolytic degreasing step, a first water washing step, a neutralization step, and a second water washing step in that order. A 5% NaOH aqueous solution was used as the alkaline electrolytic degreasing solution, an Au-Sn solder material was used as the cathode, and the current density was set to 2 A / dm 2 The alkaline electrolytic degreasing treatment was performed in two stages with the immersion time set to 15 seconds, and the line speed was set to continuously perform the alkaline electrolytic degreasing treatment on the ribbon-shaped Au-Sn solder material.

[0034] In Example 2, the current density was 3.5 A / dm2 The alkaline electrolytic degreasing treatment was carried out under the same conditions as in Example 1, except that the temperature was set to 100° C.

[0035] In Example 3, the current density was 5 A / dm 2 The alkaline electrolytic degreasing treatment was carried out under the same conditions as in Example 1, except that the temperature was set to 100° C.

[0036] In Example 4, the current density was 0.7 A / dm 2 The alkaline electrolytic degreasing treatment was carried out under the same conditions as in Example 1, except that the temperature was set to 100° C.

[0037] In Example 5, the current density was 7 A / dm 2 The alkaline electrolytic degreasing treatment was carried out under the same conditions as in Example 1, except that the temperature was set to 100° C.

[0038] In Example 6, one alkaline electrolytic degreasing treatment was performed, and the current density was 5 A / dm 2 The alkaline electrolytic degreasing treatment was carried out under the same conditions as in Example 1, except that the temperature was set to 100° C.

[0039] In Comparative Example 1, instead of the alkaline electrolytic degreasing treatment of Example 1, a commercially available paraffin-based hydrocarbon cleaner NS Clean 100 was used to clean ribbon-shaped Au-Sn solder material with an immersion time of 60 seconds and ultrasonic waves of 40 kHz and 100 W applied.

[0040] Next, the washed solder material was punched out using a die with a press machine to obtain a frame-shaped Au-Sn alloy solder material with an outer diameter of 1.0 x 0.8 mm, an inner diameter of 0.86 x 0.66 mm, a frame width of 0.07 mm, and a thickness of 0.015 mm.

[0041] These frame-shaped Au-Sn alloy solder materials were melted and solidified by heating at 300°C for 5 minutes on an Au-plated Kovar plate with an oxygen concentration of 5 ppm or less, and the height of the four corners and the frame width of the sides of 10 solder materials produced under each condition in Examples 1 to 6 and Comparative Example 1 were measured, and the average value was calculated. The measurement points are shown in Figure 3. The measurement and calculation results are shown in Tables 1 and 2. Table 1 shows the maximum height of the four corners, the average height of the four corners, the difference in height of the four corners (maximum value - minimum value), and the maximum height / plate thickness. Table 2 shows the maximum width of the four corners and the maximum width / set width. The width of the corners was the distance from the corner of the outer shape to the corner of the inner shape. The set width of the corners was the design value of the corners of the frame shape. In the punching process of the frame shape in this example and comparative example, the set value of the corners of the frame shape was 91 μm.

[0042] As shown in Tables 1 and 2, it was found that the solder material subjected to the alkaline electrolytic degreasing treatment of the present invention had improved wettability with Au-Sn solder and was able to maintain its shape with high precision when the solder material was melted.

[0043] [Table 1]

[0044] [Table 2]

Claims

1. The solder material for joining electronic components is made of a gold-based alloy and has a frame shape with outer dimensions of 1.2 mm square or less, a thickness of 0.02 mm or less, and a frame width of 0.15 mm or less, or a ring shape with an outer diameter of φ1.2 mm or less and a thickness of 0.02 mm or less, and is characterized in that the maximum height of the solder material after being heated to melt and solidify is within twice the thickness of the solder material before heating.

2. 2. The gold-based alloy solder material according to claim 1, characterized in that the solder material has a frame shape, and the difference in height between the four corners of the solder material after it has been heated to melt and solidify is equal to or less than the thickness of the solder material before heating.

3. 3. The gold-based alloy solder material according to claim 1, characterized in that the solder material has a frame shape, and the maximum width of the four corners of the solder material after it has been heated to melt and solidify is within twice the width of the four corners of the solder material before heating.

4. 4. The gold-based alloy solder material according to claim 1, which is made of an Au-Sn alloy and has a frame shape with outer dimensions of 1.0 mm square or less, a thickness of 0.015 mm or less, and a frame width of 0.15 mm or less.

5. A method for producing a solder material for joining electronic components, comprising the steps of: mixing gold as the main component with Sn in a desired ratio; melting this to produce an Au-20wt%Sn alloy; casting the alloy into a thin plate; rolling the alloy into a ribbon shape; and using an aqueous sodium hydroxide solution to perform an alkaline electrolytic degreasing process at a current density of 0.7 to 7A / dm2 using the solder material as the cathode. The solder material is then shaped into a frame shape with outer dimensions of 1.2 mm square or less, a thickness of 0.02 mm or less, and a frame width of 0.15 mm or less, or into a ring shape with an outer diameter of φ1.2 mm or less and a thickness of 0.02 mm or less, thereby producing a solder material whose maximum height after heating, melting, and solidifying is within twice the thickness of the solder material before heating.

6. 6. The method for producing a gold-based alloy solder material according to claim 5, wherein the alkaline electrolytic degreasing treatment is carried out in two stages.

7. The alkaline electrolytic degreasing treatment is carried out at 2 to 5 A / dm 2 7. The method for producing a gold-based alloy solder material according to claim 5, wherein the current density is 1000 .mu.m.

8. The method for manufacturing a gold-based alloy solder material according to any one of claims 5 to 7, characterized in that the solder material after the shaping process has a frame shape with outer dimensions of 1.0 mm square or less, a thickness of 0.015 mm or less, and a frame width of 0.15 mm or less.

Citation Information

Patent Citations

  • Preparation method for AuSn20 alloy brazing filler metal used for packaging integrated circuit and usage thereof

    CN102114584A

  • Gold-tin alloy brazing filler metal having excellent wettability

    JP2001150182A

  • Brazing filler metal

    JP2002283094A

  • JOINING METHOD WITH Au-Sn BASED BRAZING FILLER METAL

    JP2005262317A

  • Brazing filler metal, device and its manufacturing method

    JP2008200706A